Molecular determinants for enzalutamide-induced transcription in prostate cancer. Issue 19 (10th September 2019) - Yuan, Fuwen; Hankey, William; Wu, Dayong; Wang, Hongyan; Somarelli, Jason; Armstrong, Andrew J; Huang, Jiaoti; Chen, Zhong; Wang, Qianben
Abstract: Enzalutamide, a second-generation androgen receptor (AR) antagonist, has demonstrated clinical benefit in men with prostate cancer. However, it only provides a temporary response and modest increase in survival, indicating a rapid evolution of resistance. Previous studies suggest that enzalutamide may function as a partial transcriptional agonist, but the underlying mechanisms for enzalutamide-induced transcription remain poorly understood. Here, we show that enzalutamide stimulates expression of a novel subset of genes distinct from androgen-responsive genes. Treatment of prostate cancer cells with enzalutamide enhances recruitment of pioneer factor GATA2, AR, Mediator subunits MED1 and MED14, and RNA Pol II to regulatory elements of enzalutamide-responsive genes. Mechanistically, GATA2 globally directs enzalutamide-induced transcription by facilitating AR, Mediator and Pol II loading to enzalutamide-responsive gene loci. Importantly, the GATA2 inhibitor K7174 inhibits enzalutamide-induced transcription by decreasing binding of the GATA2/AR/Mediator/Pol II transcriptional complex, contributing to sensitization of prostate cancer cells to enzalutamide treatment. Our findings provide mechanistic insight into the future combination of GATA2 inhibitors and enzalutamide for improved AR-targeted therapy.